MAPANIA (CYPERACEAE) OF HEART OF BORNEO PROJECT AREA, SARAWAK - Meekiong, Kalu; Shabdin, Z.; Miraadila, M.I.; Ivy Geradlyn, N.; Yahud, W.; Yazid, K.; Nur Safinas, J.; Aimi Syazana, Sedek; Syauqina, M.Y. (2019)
The occurrences and diversity of Mapania species in the Heart of Borneo (HoB) project areas were presented. Five selected localities namely Lanjak Entimau Wildlife Sanctuary (LEWS), Ulu Baleh National Park (UBNP), Ulu Mentawai, Mulu National Park (UMMNP), Long Banga (LB) and Tama Abu Production Forest (TAPF) were surveyed during the HoB Scientific Expeditions (2008 - 2017). A total of 27 taxa (25 species) were recorded including new discovery species (M. angustifolia, M. ballehensis, M. kipas, M. mirae, M. obscuriflora and M. sapuaniana) and three undetermined species (Mapania sp.2, sp.4 and sp.9). The LEWS and UBNP that located in Kapit Division shows a greater number of species collected compared others from the eastern north site. The diversity of Mapania species in the HoB areas is considered high with about 67.5% from a total number recorded in Sarawak. As many places are yet to be surveyed, the diversity of Mapania in the HoB areas might be reaching more than 40 taxa.